Understanding mechanisms of change: An unpacking study of the evidence-based common-elements treatment approach (CETA) in low and middle income countries. (July 2020) - Murray, Laura K.; Haroz, Emily; Dorsey, Shannon; Kane, Jeremy; Bolton, Paul A.; Pullmann, Michael D.
Abstract: There is a recognized need to better understand "essential ingredients" of psychological treatments, and refine interventions to be more scalable and sustainable. The goal of the present study was to look within a specific modular, flexible, multi-problem transdiagnostic psychological intervention –the Common Elements Treatment Approach (CETA) - and examine questions that would lead to optimizing CETA for scale up and sustainment. Utilizing data from two trials of CETA in two different countries (Thailand and Iraq), this manuscript aims to: 1) determine the "active treatment dose" or how many sessions are needed to achieve clinically meaningful change overall, in CETA); and 2) test how trajectories of client symptom change varied based on client characteristics and/or on delivery of certain elements. Results showed that overall 50% of CETA clients show some improvement after 4–6 sessions (1 SD) and large improvement (2 SD) after 7–10 sessions. Trajectories of change show steady symptom decline over time. Results support gradual exposure as one of the "active ingredients". Findings suggest that modular, flexible transdiagnostic models may allow for more efficient, targeted treatment as we gain more knowledge about key ingredients, their timing within treatment, and client outcomes. Highlights: Trajectories of change slow steady symptom decline over time. Half of clients show some improvement after 4–6 sessions, and more after 7–10. Gradual exposure is an active ingredient for trauma populations. Longitudinal measurement could promote the study of mechanisms of change. Modular flexible transdiagnostic models may allow for more efficient treatment.